Analysis of Slow Coal Loading in MV. Placid Sea at Tabone Anchorage - Markus Asta Patma Nugraha; Redy Yudanto (International Journal of Social Service and Research, 2022)
PT. Indo Dharma Transport Banjarmasin is located in South Kalimantan and is one of Indonesia's best ship agency companies. This research aims to determine the factors that cause the slow process of transferring or loading coal from barges to large ships on MV. Placid Sea in Taboneo Anchorage, Banjarmasin, and to find out how to minimize the loading time of coal from barges to large ships. This research was conducted at PT. Indo Dharma Transport Banjarmasin. This type of qualitative descriptive research is the result of research in the form of data not stated in numbers but presented in the form of a narrative. The results showed the slow process of transferrin or loading coal from barges to large ships on MV. The Placid Sea in Taboneo Anchorage was due to several factors that hindered the loading process, including damage to the loading and unloading equipment, bad weather, and the slow process of barging berthing. Therefore, periodic maintenance and checks on loading and unloading equipment are needed to avoid damage during the loading process and assist tug boats in barging and berthing.